3-(3,4-Dihydroxyphenyl)adenine, a urinary DNA adduct formed in mice exposed to high concentrations of benzene - Mikeš, Petr; Sístek, Václav; Krouželka, Jan; Králík, Antonín; Frantík, Emil; Mráz, Jaroslav; Linhart, Igor (Journal of applied toxicology, 2013)
Metabolism of benzene, an important environmental and industrial carcinogen, produces three electrophilic intermediates, namely, benzene oxide and 1,2- and 1,4-benzoquinone, capable of reacting with the DNA. Numerous DNA adducts formed by these metabolites in vitro have been reported in the literature, but only one of them was hitherto identified in vivo. In a search for urinary DNA adducts, specific LC-ESI-MS methods have been developed for the determination in urine of six nucleobase adducts, namely, 7-phenylguanine, 3-phenyladenine, 3-hydroxy-3,N(4) -benzethenocytosine, N(2) -(4-hydroxyphenyl)guanine, 7-(3,4-dihydroxyphenyl)guanine and 3-(3,4-dihydroxyphenyl)-adenine (DHPA), with detection limits of 200, 10, 260, 50, 400 and 200 pg ml(-1) , respectively. Mice were exposed to benzene vapors at concentrations of 900 and 1800 mg m(-3) , 6 h per day for 15 consecutive days. The only adduct detected in their urine was DHPA. It was found in eight out of 30 urine samples from the high-exposure group at concentrations of 352 ± 146 pg ml(-1) (mean ± SD; n = 8), whereas urines from the low-exposure group were negative. Assuming the DHPA concentration in the negative samples to be half of the detection limit, conversion of benzene to DHPA was estimated to 2.2 × 10(-6) % of the absorbed dose. Thus, despite the known high mutagenic and carcinogenic potential of benzene, only traces of a single DNA adduct in urine were detected. In conclusion, DHPA is an easily depurinating adduct, thus allowing indication of only high recent exposure to benzene, but not long-term damage to DNA in tissues.
Keywords: Chromatography, High Pressure Liquid; Adenine; referenční standardy; Administration, Inhalation; Benzene; Biomarkers; zvířata; myši; benzen; Mice; Reference Standards; hmotnostní spektrometrie s elektrosprejovou ionizací; adenin; biologické markery; Male; Carcinogens; karcinogeny; aplikace inhalační; Spectrometry, Mass, Electrospray Ionization; Animals; mužské pohlaví; adukty DNA; hmotnostní spektrometrie; DNA Adducts; vysokoúčinná kapalinová chromatografie; Mass Spectrometry